Electron Transfer Pathways in Cytochrome c Oxidase - Lucas, M. Fátima (2011)
Mixed quantum mechanical/molecular mechanics calculations, were used to explore the electron pathway of the terminal electron transfer enzyme, Cytochrome c Oxidase. This enzyme catalyzes the reduction of molecular oxygen to water in a multiple step process. Density functional calculations on the three redox centers allowed for the characterization of the electron transfer mechanism, following the sequence Cu(A) → heme a → heme a(3). This process is largely affected by the presence of positive charges, confirming the possibility of a proton coupled electron transfer. An extensive mapping of all residues involved in the electron transfer, between the Cu(A) center (donor) and the O(2) reduction site heme a(3)-Cu(B) (receptor), was obtained by selectively activating/deactivating different quantum regions. The method employed, called QM/MM e-pathway, allowed the identification of key residues along the possible electron transfer paths, consistent with experimental data. In particular, the role of arginines 481 and 482 appears crucial in the Cu(A) → heme a and in the heme a → heme a(3) electron transfer processes.